Efficacy of wrist robot-aided orthopedic rehabilitation: a randomized controlled trial - Albanese, Giulia Aurora; Taglione, Elisa; Gasparini, Cecilia; Grandi, Sara; Pettinelli, Foebe; Sardelli, Claudio; Catitti, Paolo; Sandini, Giulio; Masia, Lorenzo; Zenzeri, Jacopo (Journal of neuroEngineering and rehabilitation, 2021)
In recent years, many studies focused on the use of robotic devices for both the assessment and the neuro-motor reeducation of upper limb in subjects after stroke, spinal cord injuries or affected by neurological disorders. Contrarily, it is still hard to find examples of robot-aided assessment and rehabilitation after traumatic injuries in the orthopedic field. However, those benefits related to the use of robotic devices are expected also in orthopedic functional reeducation.